Leprosy revealed in a rheumatology clinic: A case series. (31st August 2012) - Prasad, Shiva; Misra, Ramnath; Aggarwal, Amita; Lawrence, Able; Haroon, Nigil; Wakhlu, Anupam; Krishnani, Narendra; Agrawal, Vinita; Paliwal, Vimal K.; Jha, Sanjeev; Agarwal, Vikas
Abstract Aim Leprosy classically presents with cutaneous and neural involvement. Rheumatological manifestations are frequent, although often under‐recognized. At times, these may present to a rheumatology clinic prior to the diagnosis of leprosy. Herein, we present our experience with patients referred with various rheumatological disorders who were subsequently diagnosed as having leprosy. Methods This retrospective study (January 2001–September 2010) was carried out at the Department of Clinical Immunology, Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, in northern India. Patients who were confirmed as having leprosy were included. Details regarding demographic and clinical presentations were collected. Results Forty‐four cases (30 male, mean age 40 ± 13.6 years and mean disease duration 18.7 ± 24.3 months) were identified. Musculoskeletal manifestations included arthritis (n = 22), swollen hands and feet syndrome (SHFS) (n = 11), tenosynovitis (n = 9), painful swollen feet (n = 9), arthralgias (n = 7) and vasculitis (n = 1). Distribution of joints mimicked rheumatoid arthritis (n = 14) and spondyloarthropathy (n = 7). Arthritis and/or tenosynovitis were part of spontaneous onset lepra reaction in 28 cases. Other clinical manifestations were: paresthesias (n = 28), erythematous nodules (n = 25) and anesthetic patches (n = 7). Thirty‐one patients had thickened nerves (ulnar n = 28, common peroneal n = 21). Eight patients did not have any cutaneous manifestations and had presented with SHFS and arthritis or tenosynovitis. These were labeled as pure neuritic leprosy. Most of the patients responded to multidrug anti‐leprosy therapy and glucocorticoids. Conclusion Rheumatological presentations of leprosy may mimic RA, spondyloarthropathy or vasculitis. Pure neuritic variety and spontaneous type 2 lepra reaction pose unique diagnostic challenges. Increased awareness may avoid delay in diagnosis.